A Stylistic Forensic Analysis of Mahira’s Suicade Notes - Ester Febrina Br Sitepu; Klara Christin Manao; Niche Orinda Br Sitompul; Anita Lasmaria Situmeang; Saranovayanti Lumban Gaol; Indah Riah Ukur Surbakti; Rahmadsyah Ranggkuti (Journal on Education, 2023)
This research aims to analyze forensic stylistics which depicts a female student who left a suicide note. This research not only focuses on stylistic forensic analysis, but also deals with linguistic elements and their influence on the social environment. This research uses qualitative methods. The focus of stylistic analysis in a forensic context is the understanding and interpretation of language that is difficult to understand. The content of the forensic linguistic text of a student's suicide note is a problem regarding writing that is not appropriate to the context, therefore this research also proposes several main categories of writing, namely writing discrimination, author identification, author characterization, and determination of author intent. Apart from that, the vocabulary used in these notes is not usually spoken by Mahira.